Intensifikasi Jalur Transportasi Nelayan Melalui Sosialisasi Rute Pelayaran Efektif Berbasis Medan Di Kelurahan Sembulang - Luthfiya Ratnasari; Siti Noor Chayati; Farouki Dinda Rassarandi; Muhammad Zainuddin Lubis; Wenang Anurogo; Sudra Irawan; Okatvianto Gustin; Arta Uly Siahaan; Riki Riki; Rizki Widi Pratama; Fadli Suandi; Swono Sibagariang; Arif Roziqin (Pusat P2M Politeknik Negeri Batam, 2021)
Sembulang Village has high potential from marine resources, tourism, to the potential geographical position that supports inter-island shipping lanes. This presents sourced its challenges to make the most of the existing economic potential while maintaining the ecological potential to achieve sustainable coastal development. Practical skills possessed by fishermen in K Sembulang Village become important provisions in the realization of sustainable development, but this needs to be harmonized with the support of various scientific backgrounds. Terrain complex analysis is able to accommodate various considerations in identifying the best sea transportation routes while minimizing negative effects on the environment. Based on these advantages carried out socialization to fishermen who are in Kelurahan Sembulang. From the activities that were successfully held, feedback obtained from participants' satisfaction with the provision of material reached 89.67%, scientific benefit aspects for the residents amounted to 87.29%, facilities supporting activities valued at 84.28%, while as much as 96.77% residents wanted similar activities to be held again in Kelurahan Sembulang.